2015
DOI: 10.15587/1729-4061.2015.51399
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of open space fire extinguishing with flammable liquid fighting aerosols

Abstract: Кандидат технических наук, доцент Львовский государственный университет безопасности жизнедеятельности ул. Клепаровская,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
(4 reference statements)
1
4
0
1
Order By: Relevance
“…Thus, the authors of paper [10] indicate that when burning alcohol in a deco with a diameter of 0.5 m, radiation occurs in the range of 11-14 kW/m 2 , which is less than for a hydrocarbon flame of this size by 25-30 %. However, paper [10] indicates that ethanol fires with the addition of gasoline over an area of 254 m 2 are characterized by a significant heat flow, even larger than when burning gasoline, which correlates with the data reported in [8,9].…”
Section: Literature Review and Problem Statementsupporting
confidence: 84%
See 1 more Smart Citation
“…Thus, the authors of paper [10] indicate that when burning alcohol in a deco with a diameter of 0.5 m, radiation occurs in the range of 11-14 kW/m 2 , which is less than for a hydrocarbon flame of this size by 25-30 %. However, paper [10] indicates that ethanol fires with the addition of gasoline over an area of 254 m 2 are characterized by a significant heat flow, even larger than when burning gasoline, which correlates with the data reported in [8,9].…”
Section: Literature Review and Problem Statementsupporting
confidence: 84%
“…No less important is the ability of fire-extinguishing aerosol to effectively extinguish combustible liquids in open space. Thus, work [8] describes the process of the successful extinguishing of the 21B standard fire by a jet aerosol in the open space. Unlike foaming agents, the fire-extinguishing aerosol has low fire extinguishing concentrations, long shelf life, low cost, is environmentally acceptable, and, after extinguishing, it is neutralized naturally in the environment.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In article [17], it is indicated that the addition of nitrogen leads to a significant decrease in the fire-extinguishing concentration of hladone 1301, for n-heptane, while maintaining all useful properties of the components. Paper [18] clearly states that the fire extinguishing effectiveness of the mixture of inhibitors and retardants significantly increases due to synergy among them [18][19][20][21][22][23]. Paper [19] presents calculations of flame temperature at addition of inert gases to a mixture of inhibitor and flegmatizer.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Paper [18] clearly states that the fire extinguishing effectiveness of the mixture of inhibitors and retardants significantly increases due to synergy among them [18][19][20][21][22][23]. Paper [19] presents calculations of flame temperature at addition of inert gases to a mixture of inhibitor and flegmatizer. They showed a decrease in flame temperature, which in turn provides enhancing of inhibiting effect of the mixture of hladone-1301 and СО 2 .…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Літературний огляд В роботі [6] описано горіння полярних рідин на відкритій поверхні та вказано особливості протікання процесу горіння в резервуарах. Спирти та їх суміші, як правило, горять без потужного інфрачервоного випромінювання, що забезпечує ефективне потрапляння дисперсної вогнегасної речовини в полум'я за рахунок зменшення інтенсивності висхідних потоків [7], але при підшаровому подаванні вогнегасного аерозолю відбувається і значне зменшення інтенсивності інфрачервоного випромінювання завдяки поглинанню частинками вогнегасного аерозолю випромінювання та дозволяє виключити з процесу гасіння етапи підготовки пінної атаки та охолодження, що передбачається при гасінні резервуарів [8]. Таким чином для підшарового гасіння горіння вуглеводневих палив та зокрема спиртів можна використовувати вогнегасні засоби об'ємної вогнегасної діївогнегасні аерозолі та їх бінарні суміші з газами -CO 2 , N 2 та інші.…”
unclassified